Age at menarche and risk of gestational diabetes mellitus: a population-based study in Xiamen, China - Liying Wang; Bing Yan; Xiulin Shi; Haiqu Song; Weijuan Su; Bingkun Huang; Yuxian Zhang; Shunhua Wang; Fuping Lv; Mingzhu Lin; Xuejun Li (BMC, 2019)
Abstract Background It has been reported that earlier age at menarche is associated with a higher risk for type 2 diabetes mellitus. However, the relationship between age at menarche and gestational diabetes mellitus is inconsistent across studies. We hypothesized that an earlier age at menarche would predict the gestational diabetes mellitus risk. Methods This was a population-based, retrospective cohort study of 70,041 women aged 18 to 53 years old, conducted between 2011 and 2018. The subjects were recruited from the Medical Birth Registry in Xiamen, China. Age at menarche was categorized as 8-12, 13, 14, 15, 16-19 years old. Logistic regression analysis and spline analysis was used to assess the risk of the menarche age group for gestational diabetes mellitus. Linear regression analysis was performed to evaluate independent associations between age at menarche and fasting plasma glucose and blood glucose 1 hour and 2 hours after a 75-g of glucose load between 24 and 28 weeks' gestation. Results The overall prevalence of GDM was 17.6%. After adjustment for family history of diabetes, earlier age at menarche (8-12, and 13 years old) was associated with increased odds for GDM (OR, 1.08; 95% CI, 1.02-1.15, and OR, 1.07; 95% CI, 1.03-1.14, respectively) compared with average age at menarche (14 years old). With further adjustment for pre-pregnancy body mass index, blood pressure, educational level, age at delivery, and hepatitis B surface antigen status, this association was attenuated (OR, 0.93, and OR, 1.02, respectively). Multivariable-adjusted spline regression models showed a linear dose-response association between age at menarche and GDM (P for nonlinearity, 0.203; P for linearity, 0.006). On linear regression analysis, earlier age at menarche was significantly associated with increased blood glucose one and 2 hours after a glucose load but not with the fasting plasma glucose. Conclusions As expected, early age at menarche was found to be associated with an increased risk of gestational diabetes mellitus. However, this association may be mediated by potential confounding factors other than age. An additional finding was that earlier menarche was significantly related with elevated pregnancy glucose concentrations after a glucose load.